Heterosynaptic plasticity induced by intracellular tetanization in layer 2/3 pyramidal neurons in rat auditory cortex - Lee, Christopher M (Blackwell Science Inc, 2012)
Associative Hebbian-type synaptic plasticity underlies the mechanisms of learning and memory; however, Hebbian learning rules lead to runaway dynamics of synaptic weights and lack mechanisms for synaptic competition. Heterosynaptic plasticity may solve these problems by complementing plasticity at synapses that were active during the induction, with opposite-sign changes at non-activated synapses. In visual cortex, a potential candidate mechanism for normalization is plasticity induced by a purely postsynaptic protocol, intracellular tetanization. Here we asked if intracellular tetanization can induce long-term plasticity in auditory cortex. We recorded excitatory postsynaptic potentials (EPSPs) of regular (n = 76) and all-or-none (n = 24) type in layer 2/3 pyramidal cells in slices from rat auditory cortex. After intracellular tetanization, 32 of 76 regular inputs (42%) showed long-term depression, 21 inputs (28%) showed potentiation and 23 inputs (30%) did not change. The direction of plasticity correlated with the initial release probability: inputs with initially low release probability tended to be potentiated, while inputs with high release probability tended to be depressed. Thus, intracellular tetanization had a normalizing effect on synaptic efficacy. Induction of plasticity by intracellular tetanization required a rise of intracellular [Ca(2+)], because it was impaired by chelating intracellular calcium with EGTA. The long-term changes induced by intracellular tetanization involved both pre- and postsynaptic mechanisms. EPSP amplitude changes were correlated with changes of release indices: paired-pulse ratio and the inverse of the coefficient of variation (CV(−2)). Furthermore, at some all-or-none synapses, changes of averaged response amplitude were correlated with a change of the failure rate, without a change of the synaptic potency, measured as averaged amplitude of successful responses. Presynaptic components of plastic changes were abolished in experiments with blockade of NO-synthesis and spread, indicating involvement of NO signalling. These results demonstrate that the ability of purely postsynaptic challenges to induce plasticity is a general property of pyramidal neurons of both auditory and visual cortices.